(untitled) (REMUNOM, 2026)
This article aimed to understand the role of relational capabilities in the process of value creation and capture in startups. An integrative review structured conceptually was used, with searches in Web of Science and Scopus databases. Sixteen articles were selected, classified into five categories: coordination, cultural, knowledge, technology, and co-adaptation. Studies demonstrated the importance of knowledge integration and interaction between partners, identifying a significant positive impact of relational capabilities on startups’ relationships with other organizations. Organizations and startups invest in value creation and capture to strengthen themselves, better serve their customers, and achieve competitive advantage. Relational capabilities constitute a source of learning and competitive advantage. With support from other companies, startups can grow and become more stable. As a contribution, the study provides an integrative framework developed from the analyzed literature and points to research perspectives for advancing knowledge on the topic.